2022
DOI: 10.24018/ejeng.2022.7.2.2786
|View full text |Cite
|
Sign up to set email alerts
|

Solar Radiation Prediction using Ant Colony Optimization and Artificial Neural Network

Abstract: This paper proposes a Solar Radiation Prediction Model employing Ant Colony Optimization (ACO) and Artificial Neural Network (ANN), named as SRPM. SRPM aims to incorporate the Feature Selection (FS) technique in the ANN training with the guidance of hybridizing ACO. The main reason behind using FS technique is, it can provide an improved solution from a particular problem by identifying the most salient features from the available feature set. In SRPM, the hybridizing ACO search technique utilizes the informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Solar radiation prediction is heavily affected by the weather, and using an ANN to solve this problem is an accurate and applicable approach. In general, latitude, longitude, altitude, sunshine rate, and month are often used as inputs for the ANN-based prediction model [78][79][80][81][82][83][84]. (5) Determination of PV system size.…”
Section: Application Of Anns In Pv Systemsmentioning
confidence: 99%
“…Solar radiation prediction is heavily affected by the weather, and using an ANN to solve this problem is an accurate and applicable approach. In general, latitude, longitude, altitude, sunshine rate, and month are often used as inputs for the ANN-based prediction model [78][79][80][81][82][83][84]. (5) Determination of PV system size.…”
Section: Application Of Anns In Pv Systemsmentioning
confidence: 99%
“…Iqbal et al claim that the constructed SRPM model could accurately predict solar radiation at every point in the world if it were precisely trained with all necessary data from the sites. (Iqbal et al, 2022). Shboul et al concluded that the suggested ANN model could reach high levels of accuracy in forecasting solar radiation and wind speed, demonstrating that the generated prediction model may be used to construct solar/wind renewable energy systems (Shboul et al, 2021).…”
Section: Introductionmentioning
confidence: 99%